PROGNOSIS OF SWELLING LANDSLIDE MASS MOVEMENT VELOCITY UPON MATRIX ROCKS (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The article is devoted to velocity prognosis of a swelling landslide mass movement for the case when swelling processes occur and lead to decreasing of shear strength and viscosity factor. According to laboratory tests and theoretical development we obtain the results when soil's swelling processes are absent, the changes of velocity of landslide mass movement through depth is described according to quadratic equation $V_y=\rho g\left(Hy-y^2 / 2\right)\sin \alpha /\eta$, but for swelling soils the relationship is linear $V_y=\left[ y+\left(H-\sigma_{sw} /\rho g\right)\right]\sin \alpha / k \tan \Psi$.
Keywords: water-colloid bond; clay viscosity; pressure; crawl; humidity